2015
DOI: 10.17795/ajnpp-27189
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Effect of Borago officinalis (Boraginaceae) Extract in Male Rats

Abstract: Background: Medicinal plants with natural antioxidants have been shown to be beneficial in a variety of complications such as anxiety. The elevated plus-maze (EPM) is one of the most widely used models to assess anxiety in small rodents. Objectives: This study was designed to characterize the anxiolytic-like activity of Borago officinalis (Linnaeus, family Boraginaceae) or Borage flowers extract, using an EPM test. Materials and Methods: Male Wistar rats weighing 220-250 grams were used in the present study. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 48 publications
0
15
0
Order By: Relevance
“…Borage extract (50, 100, 200 mg/kg) before an EPM trial significantly increased the time spent in open arms and percentage of open arms entries, whereas, the extract showed no effect on the number of closed arm entries. The results indicated that IP injection of Borage extract might have an anxiolytic potential in rats [18].…”
Section: Badranjaboya (Melissa Parviflora Family -Lamiaceae)mentioning
confidence: 90%
“…Borage extract (50, 100, 200 mg/kg) before an EPM trial significantly increased the time spent in open arms and percentage of open arms entries, whereas, the extract showed no effect on the number of closed arm entries. The results indicated that IP injection of Borage extract might have an anxiolytic potential in rats [18].…”
Section: Badranjaboya (Melissa Parviflora Family -Lamiaceae)mentioning
confidence: 90%
“…In the present work we also exposed the rats to the EPM. The EPM is a widely used anxiety model [44][45][46], and has been validated by Pellow et al [35] in behavioral, physiological, and pharmacological approaches. [47].…”
Section: Discussionmentioning
confidence: 99%
“…Changes within the percentage of passage on to the open arena and time spent on these arena are regarded as reliable correlates of changes in the amount of anxiety in experimental models. Therefore, the EPM is advised as a validated and reliable device to reflect both anxiolyticand anxiogenic-like effects of various drugs ( Pellow, et al, 1985 ; Pellow and File, 1986 ; Komaki, et al, 2014a ; Komaki, et al, 2015b ; Nemati, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%